Pemanfaatan Artifical Intelegence (AI) Guna Peningkatan dan Memperkaya Kecakapan Digital Dikalangan Siswa - Deden Rosid Waltam; Wawan Budiarto; Bambang Herlambang (Lembaga Pengembangan Kinerja Dosen, 2026)
The Artificial Intelligence (AI) Utilization Training represents a structured community service initiative targeting students of Rumah Yatim and Pesantren Ruhama. This program is designed to equip participants with additional competencies, encompassing practical skills and contemporary digital literacy aligned with the evolving demands of the educational sector. The AI utilization training aims to enhance students’ digital literacy, thereby fostering their capacity to adapt to emerging technological advancements. Participants are trained to comprehend foundational AI concepts and their applications in learning, productivity, and innovation, contributing to their preparedness for the Industrial Revolution 4.0 and Society 5.0. Observations conducted in collaboration with partner institutions identified several challenges, including limited student engagement in digital literacy, insufficient infrastructure, and a lack of understanding regarding AI utilization. In response, this program implements targeted workshops and training sessions focused on AI applications. The activities undertaken in this program include: (1) facilitating access to AI applications and providing instructional guidance to enable students to acquire fundamental digital skills with minimal barriers; and (2) delivering interactive, engaging, and easily comprehensible instruction on basic AI applications through practical demonstrations and hands-on exercises. This initiative is expected to promote the development and enrichment of students’ competencies in both theoretical and practical dimensions of digital literacy. Consequently, participants demonstrate improved proficiency and confidence in AI utilization, enhancing their readiness to navigate current and future digital technology landscapes. Empirical outcomes indicate an increase in participants’ knowledge, understanding, skills, and competency related to AI from 85% prior to training to 95% post-training.